Al factorizar 225x2−289y2 se obtiene: (15x17y)(15x+17y) (15x−17y)(15x+17y) (15x+17y)(15x+17y) (15x−17y)2
Respuestas
Respuesta dada por:
5
Es diferencia de cuadrados:
![225 {x}^{2} - 289 {y}^{2} = \\ {(15x)}^{2} - {(17y)}^{2} = \\ (15x - 17y)(15x + 17y) 225 {x}^{2} - 289 {y}^{2} = \\ {(15x)}^{2} - {(17y)}^{2} = \\ (15x - 17y)(15x + 17y)](https://tex.z-dn.net/?f=225+%7Bx%7D%5E%7B2%7D++-+289+%7By%7D%5E%7B2%7D++%3D++%5C%5C++%7B%2815x%29%7D%5E%7B2%7D++-++%7B%2817y%29%7D%5E%7B2%7D++%3D++%5C%5C+%2815x+-+17y%29%2815x+%2B+17y%29)
Preguntas similares
hace 9 años
hace 9 años
hace 9 años